1999
DOI: 10.1080/10408449991349195
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Biomarkers in Environmental Health Studies: The Case of PAHs and Benzene

Abstract: Exposure biomarkers, which have long been restricted to the framework of occupational hygiene, currently arouse increasing interest in the field of environmental pollution. To assess their validity, we propose here a conceptual framework that is based on their intrinsic characteristics and on properties related to the procedures for their analysis. The most important criteria are specificity for the toxic substance under consideration and sensitivity, that is, the ability to distinguish contrasted levels of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(58 citation statements)
references
References 119 publications
(162 reference statements)
1
56
1
Order By: Relevance
“…The same test with the pure 1,6-or 1,8-pyrenequinone indicates that the mutagenicity of the mixture is not from the quinoes, but from other unknown oxygenated photoproducts. Hydroxy-PAHs are the oxidative metabolites commonly detected in the urine of animals or humans exposed to PAHs and are often used as biomarkers (11,76). Among them, 1-hydroxypyrene (HP) is the most widely used biomarker for PAH exposure (17,(76)(77)(78)(79)(80)(81).…”
Section: Pah Photochemistrymentioning
confidence: 99%
“…The same test with the pure 1,6-or 1,8-pyrenequinone indicates that the mutagenicity of the mixture is not from the quinoes, but from other unknown oxygenated photoproducts. Hydroxy-PAHs are the oxidative metabolites commonly detected in the urine of animals or humans exposed to PAHs and are often used as biomarkers (11,76). Among them, 1-hydroxypyrene (HP) is the most widely used biomarker for PAH exposure (17,(76)(77)(78)(79)(80)(81).…”
Section: Pah Photochemistrymentioning
confidence: 99%
“…Studies have shown significant correlations between urinary 1-OHP concentrations and occupational and environmental exposure to all PAH or pyrene concentrations [7][8][9][10][11] . Factors that may cause inter-individual differences in urinary 1-OHP levels are lifestyle factors such as smoking, alcohol consumption and dietary intake 12) ; personal factors such as age, sex and body mass index (BMI) 13) ; and airborne PAH concentrations in hightraffic areas 14) .…”
mentioning
confidence: 99%
“…In earlier studies where 1-HP has been measured, it has been applied as an index substance of PAHs (Dor et al 1999). Major attention has been paid to malignant diseases (Boffetta et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…One of these is pyrene, which is metabolized into 1-hydroxypyrene (1-HP), which in turn is conjugated to a major part with glucuronide or sulfate, and excreted in urine (Singh et al 1995). Urinary 1-HP is suggested to be the most relevant parameter for estimating individual exposure to PAHs (Dor et al 1999). …”
Section: Introductionmentioning
confidence: 99%